2021
DOI: 10.3390/ijms22126636
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phytochemicals Derived from Gymnosperms in the Prevention and Treatment of Cancers

Abstract: The incidence of various types of cancer is increasing globally. To reduce the critical side effects of cancer chemotherapy, naturally derived compounds have been considered for cancer treatment. Gymnosperms are a group of plants found worldwide that have traditionally been used for therapeutic applications. Paclitaxel is a commercially available anticancer drug derived from gymnosperms. Other natural compounds with anticancer activities, such as pinostrobin and pinocembrin, are extracted from pine heartwood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…Pinostrobin ( Figure 1 a), a dietary bioflavonoid isolated from Pinus strobus , exhibits antiviral (against herpes simplex virus-1) and antibacterial (against Helicobacter pylori ) activities. This bioflavonoid also exhibits anti-inflammatory activities, including the inhibition of the expression of tumor necrosis factor (TNF)-α, interleukin-1β, cyclooxygenase (COX)I, and COXII [ 8 ]. Furthermore, pinostrobin inhibits the formation of focal and cell adhesions to reduce the migration of malignant breast epithelial cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinostrobin ( Figure 1 a), a dietary bioflavonoid isolated from Pinus strobus , exhibits antiviral (against herpes simplex virus-1) and antibacterial (against Helicobacter pylori ) activities. This bioflavonoid also exhibits anti-inflammatory activities, including the inhibition of the expression of tumor necrosis factor (TNF)-α, interleukin-1β, cyclooxygenase (COX)I, and COXII [ 8 ]. Furthermore, pinostrobin inhibits the formation of focal and cell adhesions to reduce the migration of malignant breast epithelial cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates that pinostrobin can be used to control the progression of advanced breast cancer. Previous studies have reported that this compound exhibits no substantial cytotoxicity in drug-sensitive and drug-resistant cell lines [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pteridophytes such as Tectaria coadunata [ 17 ], different species of the genus Selaginella [ 18 ], and Adiantum philippense [ 19 ] are noteworthy for their therapeutic potential. Some members of gymnosperms, namely Pinus strobus, and Pinus pinastar are known for their antimicrobial phytocompounds [ 20 ]. Moreover, many members of the plant family Lamiaceae are found to have medicinal properties [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have pharmacological or biological activities for the treatment of cancer and other diseases. 11 One of the plant that have natural compound is melinjo (Gnetum gnemon L.). It is known that melinjo seed extract (MSE) contains trans-resveratrol (tRV); isorhapontigenin; gnetin C, gnemonosides A, C, and D and gnetin L. Melinjo seed extract (MSE) has been reported to have a broad spectrum of pharmacological effects such as anticancer, 10 inhibitory angiogenesis, antibacteria, 14 antioxidant.…”
Section: Introductionmentioning
confidence: 99%